Nile BDC hard seat—Integrated watershed management successes and innovations - Sharma, Bharat R. (International Livestock Research Institute, 2011)
In this 'hard seat' interview on 4 May 2011, Alan Duncan (ILRI) interviewed Bharat Sharma (IWMI) on integrated watershed management successes and innovations in South Asia and their relevance to Ethiopia and implications for the Nile BDC. The interview was part of the Nile Basin Development Challenge (http://nilebdc.org) 'science and reflection' workshop in Addis Ababa in May 2011.